Global Attractor of an Evolution Inclusion with Pulse Influence at Fixed Moments of Time - Kapustyan, O. V.; Perestyuk, N. A. (Ukrains’kyi Matematychnyi Zhurnal, 2003)
We consider an autonomous evolution inclusion with pulse perturbations at fixed moments of time. Under the conditions of global solvability, we prove the existence of a minimal compact set in the phase space that attracts all trajectories.